2022
DOI: 10.1088/1361-6498/ac5e50
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose to nuclear medicine technologists when operating PET/MR compared with PET/CT

Abstract: Purpose: Since 2010, PET/MR has been increasingly used for clinical routine in nuclear medicine departments. One advantage of PET/MR over PET/CT is the lower ionising radiation dose delivered to patients. However, data on the radiation dose delivered to staff operating PET/MR compared to new generation PET/CT is still lacking. Our aim was to compare the radiation dose to nuclear medicine technologists performing routine PET/MR and PET/CT in the same department. Methods: We retrospectively measured during 13 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Existing studies on this subject exhibit variations in TLD material, radiation type or energy, strength of magnetic field, and dose levels. Additionally, certain studies either omit information on the TLD material used or employ doses at the scale of radiation therapy, exceeding typical occupational doses for healthcare professionals [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies on this subject exhibit variations in TLD material, radiation type or energy, strength of magnetic field, and dose levels. Additionally, certain studies either omit information on the TLD material used or employ doses at the scale of radiation therapy, exceeding typical occupational doses for healthcare professionals [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Soret M et al reported that, for an equal injected activity to patient, the radiation dose to technologists working with PET/MR was double that of PET/CT. The difference was associated with extended contact with injected patients during patient positioning with the PET/ MR and MR coil placement, especially in whole-body studies [11]. However, electronic dosimeters were used in that study and the possible effect of the magnetic field of MRI on dosimeters was not included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Data on monthly radiation exposure doses were collected by using personal dosimeters (Chiyoda Technol, Japan) during the respective time periods. Doses were measured in sieverts (Sv) as dose equivalent Hp(10), which represents the dose equivalent in soft tissue at a depth of 10 mm (Soret et al 2022). The limit of the detection (LOD) is 0.05 mSv, and the dosimeter was exchanged on a monthly cycle.…”
Section: Methodsmentioning
confidence: 99%